Planetarium Glass Based on Augmented Reality to Improve Science Literacy Knowledge in Madura Primary Schools - Ayu, Rr. Fadila Kusumaning; Jannah, Zahrotul; Fauziah, Nur; Ningsih, Tri Nadia; Manilaturrohmah, Manilaturrohmah; Suryadi, Devaldi Akbar; Budiarti, Rizqi Putri Nourma; Fitriyah, Fifi Khoirul (Universitas Nahdlatul Ulama Surabaya, 2021)
One of the important branches of science on an international scale is scientific literacy. This study aimed to increase the science literacy knowledge of elementary school students on the material of the solar system. This study uses the ADDIE type Research and Development (R&D) method, starting from analysis, design, development, implementation, and evaluation. Expert testing of a learning product was carried out by users of the Planetarium Glass application, namely grade VI students of SDN Patengteng 2. The results of this media trial on 22 respondents showed 80% effectiveness. This research instrument uses an online questionnaire to users to determine the effectiveness of this learning media. The final result of the Planetarium Glass application media based on augmented reality is an application format that can be used by utilizing an android-based smartphone. This media provides information about the material of the solar system in the form of 3D virtual animation (3 dimensions) accompanied by an explanation of each object in audio form and is equipped with an application usage module. This media is designed to facilitate students' understanding in understanding the material of the solar system effectively and efficiently because students can see directly the material conveyed via the smartphone they use. Learning using the Planetarium Glass application can be used as an alternative learning media in increasing science literacy knowledge of elementary school students, especially in Madura.